Serum Alkaline Phosphatase, Iron and Calcium Levels in BreastCancer and Leukemia Patients in Salah Al-Din Province - M.Yonis Al-Anzy, Moayad; Ahmed Salih, Nadya (Tikrit Journal of Pharmaceutical Sciences, 2023)
This study was conducted on 19 breast cancer and 23 leukemia patients with ages ranged between 25-70 years old registered in Tikrit teaching hospital, Tikrit city, rvith the fifty four normal subject's volunteers and age ranged between 30-60 years old. Statistical analysis, show there lvere highly significant differences (p<0.05) between the mean levels of calcium, iron and alkaline phosphatase in breast cancerand leukemia compared rvith the normal strbjects. We found that the mean levels of serum calcium were higher in ler.rkemia than in breast cancer and normal subjects, also we found higher mean values of serllm iron in breast cancer compared with the leukemia and healthy subjects. The activity of the ALP 'uvas found elevated in both patients and increzrsed levels of ALP depends on the concentration of serurn iron. . We done this study to show effect of the age on calcium, iron and ALP levels in breast cancer and leukemia.